2002
DOI: 10.1111/j.1574-695x.2002.tb00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral and mucosal prime-boost immunization strategies in mice with hepatitis B surface antigen and CpG DNA

Abstract: Synthetic oligodeoxynucleotides (ODN) containing immunostimulatory CpG motifs (CpG ODN) are potent adjuvants to protein antigens administered by parenteral or mucosal routes to BALB/c mice. To date, there have been no studies using combined parenteral/ mucosal approaches with CpG DNA as adjuvant. In this study we evaluated different parenteral prime^mucosal boost and mucosal primep arenteral boost strategies using hepatitis B surface antigen (HBsAg) alone or with different adjuvants: aluminum hydroxide (alum),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
22
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(24 citation statements)
references
References 29 publications
(29 reference statements)
2
22
0
Order By: Relevance
“…DNA boost, the oral F4 boost was clearly more immunogenic for the adjuvanted groups, as judged by an enhanced isotype switching towards IgG in the spleen and increased numbers of IgG ASC in the Cerv LN. This is in agreement with other studies demonstrating that prime-boost immunizations by alternating routes and/or immunization forms are as immunogenic or more immunogenic than homologous prime-boost immunizations (Baca-Estrada et al, 2000;McCluskie et al, 2002;Lauterslager et al, 2003). As observed previously (Melkebeek et al, 2007), boosting of systemic responses in parenterally primed pigs by oral F4 administration appeared to be independent of the F4R status of the pigs.…”
Section: Discussionsupporting
confidence: 92%
“…DNA boost, the oral F4 boost was clearly more immunogenic for the adjuvanted groups, as judged by an enhanced isotype switching towards IgG in the spleen and increased numbers of IgG ASC in the Cerv LN. This is in agreement with other studies demonstrating that prime-boost immunizations by alternating routes and/or immunization forms are as immunogenic or more immunogenic than homologous prime-boost immunizations (Baca-Estrada et al, 2000;McCluskie et al, 2002;Lauterslager et al, 2003). As observed previously (Melkebeek et al, 2007), boosting of systemic responses in parenterally primed pigs by oral F4 administration appeared to be independent of the F4R status of the pigs.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, the present findings have clearly demonstrated that sG HeV -alum alone is also capable of providing complete protection from a HeV challenge. As HeV and NiV replicate and cause severe pathology in the lung and CpG motifs have been shown to elicit Th1 and mucosal immunity regardless of the immunization route used (34)(35)(36), the most recent sG vaccine studies have used and explored several CpG adjuvants. Additionally, several CpG motifs have also entered into human clinical trials, which could facilitate future regulatory processes for this adjuvant in general.…”
Section: Discussionmentioning
confidence: 99%
“…Immunogenicity studies have also shown that the combination of mucosal priming followed by systemic boosting results in high antigenspecific antibody responses (25,39,40). However, in most H. pylori vaccine/protection studies immunized animals were challenged within a month after immunization, whereas we challenged the animals 3 months after immunization (11,13,15,20,24,34,35,43).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike for Helicobacter felis, against which long-term protection can be achieved through immunization, a longterm-protection model for H. pylori has yet to be reported (27,33). Recent studies have demonstrated that immunization through a combination of mucosal and systemic routes may increase mucosal immunity (22,25,39,40).…”
mentioning
confidence: 99%